Basic researchTissue cardiomyoplasty using multi-layer cell-seeded nano-structural scaffolds to repair damaged myocardium: an experimental pilot study - Soleimani, Massoud; Mohammadi, Yousef; Ahmadbeigi, Nasser; Tafti, Hossein Ahmadi; Nassiri, Seyed Mahdi; Boroumand, Mohammad Ali; Rabbani, Shahram; Sahebjam, Mohammad; Moshtaghi, Naghmeh; Fayazzadeh, Ehsan (Archives of Medical Science, 2008)
Introduction: The emerging fields of tissue engineering and biomaterials have begun to provide potential treatment options for heart failure. Tissue engineering approaches are designed to repair damaged cardiac tissue through the use of cellular transplantation, and biodegradable scaffolds. In an experience for the first time in Iran applying nanobiotechnology in heart tissue engineering, we investigated the outcome of a multi-layer nanostructural scaffold containing cardiac and endothelial cells grafted on the infarcted heart. Material and methods: Myocardial infarction was induced in sheep by ligation of the distal portion of the left anterior descending coronary artery. Biopsy of the left ventricular cardiac muscle and jugular vein was obtained. Tissue samples were isolated and cultured in vitro . Cultured cardiac and endothelial cells were seeded onto the layers of poly(e-caprolactone)/collagen biodegradable scaffolds. After two months, the scaffold was sutured on the surface of the infarcted myocardium. Results: Eight weeks after implantation, there was remarkable thickening as well as decreased paradoxical motion of the ventricular wall in echocardiographic evaluation. There was no significant improvement in global ejection fraction. In microscopic examinations by Masson’s trichrome staining and immu-nohistochemical analysis, viable cells were observed within layers of the scaffold with incorporation of the graft into the adjacent myocardium. There were also spectacular amounts of vascularization in the grafted material. Conclusions: Our data demonstrate that engrafting of multilayer cell-seeded nanostructural scaffolds can induce angiogenesis in the implanted region. Such tissue engineered cells containing scaffolds are a promising means of tissue cardiomyoplasty in the field of regenerative medicine. Further studies are however encouraged to investigate the physiopathological aspects of heart tissue engineering.